Cortical processing of object affordances for self and others' action - Maranesi, Monica; Bonini, Luca; Fogassi, Leonardo (Frontiers in Psychology, 2014)
The perception of objects does not rely only on visual brain areas, but also involves cortical motor regions. In particular, different parietal and premotor areas host neurons discharging during both object observation and grasping. Most of these cells often show similar visual and motor selectivity for a specific object (or set of objects), suggesting that they might play a crucial role in representing the “potential motor act” afforded by the object. The existence of such a mechanism for the visuomotor transformation of object physical properties in the most appropriate motor plan for interacting with them has been convincingly demonstrated in humans as well. Interestingly, human studies have shown that visually presented objects can automatically trigger the representation of an action provided that they are located within the observer’s reaching space (peripersonal space). The “affordance effect” also occurs when the presented object is outside the observer’s peripersonal space, but inside the peripersonal space of an observed agent. These findings recently received direct support by single neuron studies in monkey, indicating that space-constrained processing of objects in the ventral premotor cortex might be relevant to represent objects as potential targets for one’s own or others' action.